TOOLS Of THE STRATEGIC FORESIGHT: USES, ABUSES AND LIMITATIONS - Pinto, Jean Paul (Cuadernos de Administración, 2008)
The characteristic throughout alI fore sight stud _shouk be the collective thought about the future Nothing replaces the human intellect in lbe construction of the future even more sophisticated  computer models. It is essential to assign most ofthe time from that provided to the analysis of variables and actors tha! allowed setting the stage. The informatics tools that come to the tools of kind MICMAC, MACTOR, MORPHOL o SMIC - PROB - EXPERT allow only save time and synthesize all information into one place for easier handling of it. Most of the time should be devoted to identifying the questions, problems and key variables for the future otherwise aH work will be lost once they have entered to software: Garbage in, Garbage out. For a better understanding of french method in the scenarios building, it should be objective starting for explain that what it means the French Scholl ofForesight.